On Second-Order Statistics of Full-Duplex Relaying - De Souza, Reginaldo Nunes; Olivo, Edgar Eduardo Benitez [UNESP]; Silva, Carlos Rafael Nogueira Da; De Freitas Ferreira, Lucas Catao; Filho, Jose Candido Silveira Santos (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Although the outage probability of full-duplex relaying communications has been extensively investigated, its outage rate and duration - crucial to the design of effective signaling schemes - remain an open problem. Herein we narrow this gap by analyzing a full-duplex, variable-gain transparent relaying protocol operating in a standard (Nakagami- m ) fading environment. We obtain exact as well as asymptotic expressions for the outage rate and duration. Also, as a byproduct, we generalize an existing asymptotic solution for the outage probability. Our results reveal that, at high transmission power, the relay-to-destination link's strength and mobility have a negligible impact on the outage rate and duration of full-duplex relaying.
Keywords: Amplify-and-forward; average fade duration; full duplex; level crossing rate; Nakagami-m fading; residual loop interference; variable gain